Etika, Moral, dan Akhlak: Pilar Utama dalam Perbankan Syariah - Noviyanti, Ririn Dwi; Romdon, Fani; Sarpini, Sarpini (FEB Universitas Maritim Semarang, 2024)
This article discusses the importance of ethics, morals and morals in the context of sharia banking in Indonesia. With increasing public awareness of sharia values, sharia banking strives to provide financial services that meet the principles of justice, transparency and social responsibility. Sharia-based business ethics not only require bankers to behave honestly, but also understand the moral norms that govern social and business interactions. Morality rooted in religious and cultural values ​​is a guideline in maintaining the integrity of financial institutions. Meanwhile, morals reflect individual character which is formed through education and experience, which is very important in maintaining the public's reputation and trust in financial institutions. This article also identifies the challenges of implementing ethics and morals in sharia banking, and provides suggestions for increasing the understanding and application of these values ​​among banking professionals. By understanding ethics, morals and manners, it is hoped that more ethical and sustainable business practices can be created so that they can make a positive contribution to society.